Basics and applications of optical interferometers integrated by femtosecond laser. Issue 3 (2nd May 2022) - Zhang, Jiawei; Sugioka, Koji
Abstract: Photonic chips have been recognized as a promising platform for information technology. On‐chip optical interferometers as fundamental building blocks of photonic chips are under extensive research with both conventional and novel fabrication techniques. Among them, recently, femtosecond laser has been attracting a great deal of attention as a powerful tool for directly writing micro‐optical devices in various materials due to its flexibility and three‐dimensional fabrication capability. This article gives a review on the working principles and recent achievements of on‐chip waveguides and interferometers fabricated by femtosecond laser, showing their potential applications in various scenarios. Abstract : Femtosecond laser inscription of optical interferometers in transparent substrates for the detection of physical quantities and substances, communication, and calculation in classical and quantum realms.